The option of last resort: A two-currency EMU - Michael G. Arghyrou; John D. Tsoukalas (Cardiff University, Cardiff Business School, 2010)
This article, originally published at www.roubini.com on 7 February 2010, spells out our two-currency EMU proposal as a plan of last resort for resolving the present EMU sovereign-debt crisis. The key ingredients of our proposal involve a temporary split of the euro into two currencies, both run by the European Central Bank. The hard euro will be maintained by the core-EMU members whereas periphery EMU countries will adopt for a suitable period of time the weak euro. All existing debts will continue to be denominated in strong-euro terms. The plan involves a one-off devaluation of the weak euro versus the strong one, simultaneously with the introduction of far-reaching reforms and rapid fiscal consolidation in the periphery EMU countries. We argue that due to enhanced market credibility, our two-tier euro plan has a realistic chance of success in resolving the EMU crisis, if all other approaches fail.
Keywords: E44; F30; G01; 330; euro; two-currency EMU; Finanzmarktkrise; Schulden; Lender of Last Resort; Währungsunion; Europäische Wirtschafts- und Währungsunion